Penggunaan Teknologi Dan Potensi Penerapan Internet Of Things (IoT) Dalam Pengembangan UMKM: Studi Kasus Resto Ayam Buldak - Wijaya, Buana Handa; Asyiqin, Akbar Dzukha; Damanuri, Aji (Invest Journal of Sharia & Economic Law, 2022)
Technology can be a facilitator in dealing with the problem of limiting social mobility. Product marketing as one of the main activities of a business unit can be done online using technology. In this journal, discussions will be conducted on the use of technology and the internet of things as facilitators in developing the Resto Ayam Buldak business unit as an innovation strategy. The business unit model began in January 2020, when the community had social restrictions due to Covid-19. The business unit of Resto Ayam Buldak is included in the category of Micro Enterprises based on the regulation of the Indonesian Law No.20 of 2008. Research in this journal is carried out by qualitative methods using substructural interview techniques to extract data and information. Based on the research results, it is known that technology supported the development of Resto Ayam Buldak during the Covid-19 pandemic. Various product information can be known through digital media, including websites, google business, grab food, food, and superfood. The collaboration of various digital technologies encourages the development of the company's image among consumers and the expansion of product marketing coverage areas. In its business process, the restaurant also uses the cashier application as an Enterprise architecture that helps make it easier for owners to control financial transactions in the business unit. The potential application of the Internet of Things IoT in controlling the production house of Resto Ayam Buldak can be made through the concept of smart production. However, the use of the Internet of Things (IoT) is still not applied in the business activities of Resto Ayam Buldak, which belongs to the Criteria for Micro Enterprises. This problem requires large investment capital to develop smart production in the business unit. The role of the government is needed in supporting technology-based creative economy activities carried out by UMKM.